Whose American Revolution was it? : historians interpret the founding - Young, Alfred F., 1925-2012; Nobles, Gregory H. (New York University Press, 2011)
The meaning of the American Revolution has always been a much contested question, and asking it is particularly important today: the standard, easily digested narrative puts the Founding Fathers at the head of a unified movement, failing to acknowledge the deep divisions in Revolutionary-era society and the many different historical interpretations that have followed. Whose American Revolution Was It? speaks both to the ways diverse groups of Americans who lived through the Revolution might have answered that question and to the different ways historians through the decades have interpreted th.